Transparent Ultrasound Transducers: From Materials to Applications - Jiaming Zhang; Guocui Bao; Shilin Hou; Fan Yang; Guo Li; Jiyan Dai (Advanced Devices & Instrumentation)
Ultrasound transducers are essential components for photoacoustic imaging (PAI) detection, which has high imaging depth and high contrast. Since conventional ultrasound transducers are opaque, complicated and bulky system designs are usually required for PAI utilizing different light and acoustic paths. To overcome the problem, transparent ultrasound transducers are highly desired, as light can transmit through transducers directly for easy alignment of light and acoustic wave. Recently, various types of transparent ultrasound transducers have been investigated for high-quality PAI. In this review, different transparent ultrasound transducers based on transparent piezoelectric materials are reviewed. Additionally, further improvement of transparent ultrasound transducers by optimization of structures of designs is discussed, and their potential applications are also discussed.